A review on polyaniline and graphene nanocomposites for supercapacitors - Idumah, Christopher Igwe (Polymer-plastics technology and engineering, 2022)
Graphene (GN), a 2-D, flat, single atomic entity, carbon allotrope, has proved to be an exceptional material recently, and garnered global accolade as a result of inherent exceptionally high charge mobility, thermally, optically, and mechanically superior attributes. In recent nanotechnological advancements, GN and its derivatives especially graphene oxide (GO) and reduced graphene oxide (r-GO) have undergone intensive investigation which has profoundly impacted on optoelectronically and electronically affiliated gadgets, chemically based sensors, nanocomposites and especially energy storage devices (ESD). GN has exhibited propensity to enhance functionalities, and performances, in addition to durabilities of numerous ESD. Conducting polymers (CPs), especially polyaniline (PANI), are polymeric materials where the chain backbone displays elevated π-conjugation in conjunction with metallically, optically, magnetically, and electronically affiliated disposition. In comparison with previously existing review papers, this paper specifically presents recently emerging advancements in synthesis, fabrication, and characterization of PANI@graphene hybrid nanocomposites with special focus on PANI@GN, PANI@GO and PANI@r-GO nanocomposites for ES applications. Market structures are also presented.